Thiamethoxam exposure deregulates short ORF gene expression in the honey bee and compromises immune response to bacteria - Decio, Pâmela [UNESP]; Ustaoglu, Pinar; Derecka, Kamila; Hardy, Ian C. W.; Roat, Thaisa C. [UNESP]; Malaspina, Osmar [UNESP]; Mongan, Nigel; Stöger, Reinhard; Soller, Matthias (Springer Nature, 2021)
Maximizing crop yields relies on the use of agrochemicals to control insect pests. One of the most widely used classes of insecticides are neonicotinoids that interfere with signalling of the neurotransmitter acetylcholine, but these can also disrupt crop-pollination services provided by bees. Here, we analysed whether chronic low dose long-term exposure to the neonicotinoid thiamethoxam alters gene expression and alternative splicing in brains of Africanized honey bees, Apis mellifera, as adaptation to altered neuronal signalling. We find differentially regulated genes that show concentration-dependent responses to thiamethoxam, but no changes in alternative splicing. Most differentially expressed genes have no annotated function but encode short Open Reading Frames, a characteristic feature of anti-microbial peptides. As this suggested that immune responses may be compromised by thiamethoxam exposure, we tested the impact of thiamethoxam on bee immunity by injecting bacteria. We show that intrinsically sub-lethal thiamethoxam exposure makes bees more vulnerable to normally non-pathogenic bacteria. Our findings imply a synergistic mechanism for the observed bee population declines that concern agriculturists, conservation ecologists and the public.